2003
DOI: 10.1186/1472-6882-3-3
|View full text |Cite
|
Sign up to set email alerts
|

Searching biomedical databases on complementary medicine: the use of controlled vocabulary among authors, indexers and investigators

Abstract: BackgroundThe optimal retrieval of a literature search in biomedicine depends on the appropriate use of Medical Subject Headings (MeSH), descriptors and keywords among authors and indexers. We hypothesized that authors, investigators and indexers in four biomedical databases are not consistent in their use of terminology in Complementary and Alternative Medicine (CAM).MethodsBased on a research question addressing the validity of spinal palpation for the diagnosis of neuromuscular dysfunction, we developed fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 13 publications
1
36
0
Order By: Relevance
“…Our data reveal that scientists are aware of these indexing inadequacies and that they use a multiple-strategy approach to overcome existing retrieval limitations. This behavior has been reported in other studies as well (Murphy et al, 2003a(Murphy et al, , 2003b. The medical group used five search TABLE 2.…”
Section: Critical Taskssupporting
confidence: 76%
“…Our data reveal that scientists are aware of these indexing inadequacies and that they use a multiple-strategy approach to overcome existing retrieval limitations. This behavior has been reported in other studies as well (Murphy et al, 2003a(Murphy et al, , 2003b. The medical group used five search TABLE 2.…”
Section: Critical Taskssupporting
confidence: 76%
“…For example, Evans 108 highlighted the particular difficulties of searching electronic databases for reports of qualitative studies arising because of the nature of the titles, the content of the abstracts and the indexing practices 111 of those preparing the databases. Evans 108 pointed out that the titles given to qualitative work, although often very descriptive of the study's focus, may not easily lend themselves to the selection of specific key terms.…”
Section: Introductionmentioning
confidence: 99%
“…Interpretation Generalizability 21 Generalizability (external validity) of trial results. Overall evidence 22 General interpretation of the results in the context of current evidence. 1.…”
mentioning
confidence: 85%
“…Studies indicate that searching for CAM-related topics is challenging due to the diversity of use of controlled vocabulary and indexing procedures between different databases [22]. It has been suggested that if authors of CAM trials (e.g., botanical medicine trials) report abstracts or titles without reference to standard controlled vocabulary, indexers may not assign appropriate indexing terms for particular studies [22,23].…”
Section: Explanationmentioning
confidence: 99%